Difference between the Decrease in P1NP Concentration and MRSS Within 3Months Treatment of Systemic Sclerosis - Devy Priyantini Hanafi (Indonesian Journal of Rheumatology, 2021)
Introduction: Systemic sclerosis is characterized by extensive and progressiveorgan fibrosis leads to organ failure and death. Progression of skin thickening is apredictor of morbidity and mortality. Due to the limitation of modified Rodnan skinscore (MRSS) sensitivity in detecting small changes in skin fibrosis, thus weproposed Procollagen Type I N-Terminal Propeptide (P1NP) as potential biomarker.This study aimed to analyze the difference between the decrease in P1NPconcentration and MRSS within 3 months treatment of systemic sclerosis.Methods: We conducted a retrospective cohort of paired numerical comparativeanalytic methods, as follow up of a study done by Vincent et al. and Dewi et al.Analyzis of MRSS changes and serum P1NP concentrations were done prior totreatment (baseline), and on week 4th, 8th and 12th treatment. Result: Fifty-ninesubjects were enrolled in the study. We analyzed the results of P1NP and MRSS at4th, 8th and 12th weeks of treatment, there was a significant decrease in meanrank of P1NP and MRSS (p=0.033 and <0.001). The effect of MRSS change wasgreater than P1NP. The highest decreasing effect of MRSS was obtained at week8th (η2 = 0.424, 42.4% decrease effect), and the largest decrease effect of P1NP wasobtained at week 12th (η2 = 0.120; 12% decrease effect). Conclusion: There was adifference in decreasing P1NP concentrations and MRSS in systemic sclerosiswithin 3 months of observation. MRSS showed a larger decrease in change thanP1NP after treatment.